Variety of Indigenous Education in the Lampung Region during the Colonization Period - Cahya, Dewi; Kumalasari, Dyah; Fahri, Ardian (Diakronika, 2023)
This article discusses the variety of indigenous education in the Lampung Region during the Colonization Period. This study aims to reconstruct past events related to indigenous education in the Lampung Region during colonization. The results of the study show that the application of ethical politics had an impact on people's lives during the colonization period. Lampung, as one of the first colonization destinations in 1905, led to the relocation of 155 families. In the early period before the arrival of the colonists from Java, the people of Lampung had implemented a concept of education in the family with inheritance carried out by parents to their children and grandchildren. The entry of Hindu-Buddhist and Islam influenced them. The variety and education system in the Javanese and Lampung colonists experienced significant developments with the emergence of the Ethical Policy policy initiated by Van Deventer. Indigenous people's education in the Colonization area of Lampung was only obtained from First Class Schools (De Scholen der Ferste Klasse), which later developed into HIS, Second Class Schools (De Scholen Der Tweede Klasse), and Village Schools (Desaschool), or People's Schools (Volkschool) and Schools. Agricultural vocational (Landbouwsclfool or Cultuurschool) Lampung does not have ELS, Europesche Lagera School, HCS, Hollands Chinese School, or Shcakel School types of schools. Meeting the needs of secondary and vocational education is only obtained from schools in Java, Palembang, or West Sumatra because, in Lampung, there are no schools such as MULO, AMS, HBS, or Higher Education in the Dutch colonial period.